Development Strategy of Religious Culture at Madrasah Tsanawiyah Negeri 2, Mojokerto, East Java - Abd. Wahib (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2023)
This research aims to describe the formulation, implementation, and evaluation of religious culture as the development of Islamic education in madrasa. This study uses a qualitative method and collects the data through observation techniques, interviews, and documentation. Data analysis uses data condensation techniques, data display, and conclusions. The results of this study are: (1) The formulation of religious culture is motivated by the existence of a community culture that needs to be internalized based on religious values so that it becomes a good habit. The purpose of religious culture from the spiritual aspect is to increase students' spirituality, and the social aspect is to shape students' character. (2) The implementation of religious culture includes